Analysis of Carrying Capacity of Water Resources Due to Land Change (Batu and Junrejo Districk) - Halimah Rahman; Zaenal Kusuma; Arief Rachmansyah (The Indonesian Green Technology Journal, 2018)
Natural resource management is one of the primary needs of all living things, both for consumption and supporting other activities. Batu City, East Java Province, is a tourist area and a water catchment area that has the potential to be a source of ground water. However, the development of infrastructure as a espoused of tourist areas need serious undermining of the sustainability of the land water source. In 2001 the environmental carrying capacity ratio was 1.75 with a conditional safe status. In 2011 and 2015 the status of environmental carrying capacity has been exceeded with a ratio of 0.85 and 0.62. In 2017 there is a conditional safe status with an environmental carrying capacity ratio of 1.24.Keywords: Demand Water Resources, Ratio of carrying capacity, Supply water resources,